Goat Farming Development Strategy in Benjor Village, Malang Regency, Indonesia - Azizah, Siti (Technium Social Sciences Journal, 2021)
The research aims were to determine strategies in farmers’ social capital strengthening to increase trust between farmers and stakeholders, in market structure, and technical-social farmers’ empowerment. The study was conducted in Benjor Village, Tumpang District, Malang Regency, and the number of respondents was 30 people. Data analysis methods used in research are SWOT analysis with IFAS (Internal Strategic Factors Analysis Summary) and EFAS (External Strategic Factors Analysis Summary) and continued with AHP (Analytic Hierarchy Process) analysis. The results of the study that the cartesian diagram position of local goat development in Benjor Village in quadrant IV, which means there are more weak points than strength points, more threat points than the opportunity points. Therefore, developing the local goat business needs to change the strategy through strengthening social capital in the trust of both other farmers with stakeholders.